Cholangiocarcinoma With Sepsis Associated With Percutaneous Transhepatic Biliary Drainage (PTBD) - Muhammad Vitanata Arfijanto; Bayu Abhiyoga (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2021)
Percutaneous transhepatic biliary drainage (PTBD) can be an alternative palliative treatment in resectable cholangiocarcinoma. One of the most common complications of PTBD is infection, with a prevalence of 3.6 – 67.4% in patients undergoing PTBD procedure, with mortality rate of 0.05-7%. We report a case of a 46-year old male with a history of fever 14 days after undergoing PTBD procedure. Physical examination revealed tachycardia, tachypnea, febris, jaundice, and decreased urine output. Laboratory results revealed hypochromic-microcytic anemia, leukocytosis, decreased renal function, elevated liver enzymes, obstructive icterus, hypoalbuminemia, and hyperkalemia. Blood and gall culture revealed a growth of Eschericia coli. The patient was given fluid resuscitation and antibiotic suitable to microbial sensitivity test, and treatment of acute kidney injury and hyperkalemia, including hemodialysis. The patient’s general condition improved after ten days of care, and was discharged on the twentieth day.  Cholangitis is one of the most infectious complications following PTBD procedure. The prevalence of sepsis in biliary drainage procedures was reported 2.5-2.7%, with enteral bacteria gram-negative bacilli being the most common pathogen found in blood and bile. The administration of prophylactic antibiotics was not proven to decrease prevalence of infection. Bacterial translocation via portal vein due to loss of mucosal integrity in the intestines may contribute to bacteremia following PTBD procedure.